Factors affecting income diversification: Special reference to paddy farming community in Anuradhapura district - Thayaparan, A.; Sandamali, A.G.A.N. (University of Jaffna, 2020)
This study focused on analyzing the determinants of income diversification among paddy farming community in Anuradhapura district. The cross – sectional data used in the study was collected from a survey done in Yala and Maha seasons in 2019/2010 which covered five villages in Galenbindunuwewa division. From each village, 30 small scale paddy farmers who were selected through multi- stage sampling technique and finally total of 150 farmers were used. Status of income diversification was taken as binary dependent variable and demographic, economic and farming characteristics were taken as independent variables. Frequency analysis, descriptive statistics and independent sample T – test were used to explore the basic features of income diversifiers and non- diversifiers across selected farmers in the study. Results of frequency showed that 84% of the farmers diversified their income and 16% of them were not diversified and independent sample t-test proved that on average, farm income, age, farming experience and distance to the market were significantly differ across diversified and non- diversified farmers in the study. To examine the determinants of income diversification, binary probit model was employed and its estimated results revealed that age of the farmer, land size and farming experience were negatively whereas marital status, farm income and ownership of land were positively impact on the income diversification at significant levels the study. The findings of the study assists to the policy makers to formulate the appropriate strategies focus on paddy farming community in the study area.
Keywords: Binary probit model; Diversifiers and non- diversifiers; Income diversification; Economic and farming characteristics